2014
DOI: 10.2147/cia.s63084
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and affective assessment in day care versus institutionalized elderly patients: a 1-year longitudinal study

Abstract: PurposeCognitive decline and depression are two common mental health problems that may create a need for long-term care among the elderly. In the last decade, the percentage of older adults who receive health care in nursing homes, day care centers, or home support services has increased in Europe. The objectives of this descriptive and nonrandomized longitudinal study were to evaluate and to compare the cognitive and affective evolution of day care versus institutionalized older patients through a 1-year peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
7
0
2
Order By: Relevance
“… 41 These authors demonstrated, after following participants for 22 years, that after controlling for numerous potential confounders, nursing home placement was significantly associated with a lower score on the MMSE and further cognitive decline, when comparing scores before and after institutionalization. Regarding language abilities, a previous report 42 demonstrated that naming function was maintained among day-care patients in comparison to institutionalized patients, who displayed reduced performance at follow-up. Similar tendencies of cognitive decline were described in Brazilian samples of institutionalized persons 43 , 44 without regular activities, who had lower scores on the MMSE 43 or the MMSE and Boston naming test when compared with institutionalized active and noninstitutionalized groups.…”
Section: Discussionmentioning
confidence: 92%
“… 41 These authors demonstrated, after following participants for 22 years, that after controlling for numerous potential confounders, nursing home placement was significantly associated with a lower score on the MMSE and further cognitive decline, when comparing scores before and after institutionalization. Regarding language abilities, a previous report 42 demonstrated that naming function was maintained among day-care patients in comparison to institutionalized patients, who displayed reduced performance at follow-up. Similar tendencies of cognitive decline were described in Brazilian samples of institutionalized persons 43 , 44 without regular activities, who had lower scores on the MMSE 43 or the MMSE and Boston naming test when compared with institutionalized active and noninstitutionalized groups.…”
Section: Discussionmentioning
confidence: 92%
“…Consistent with this view, the decline in memory that is associated with normal or pathological aging appears to be aggravated after institutionalization [ 10 , 11 ]. Institutionalization is often associated with a standard-like environment with reduced sensory-motor and cognitive stimulation, social interactions, and physical activity, which contribute to a sedentary lifestyle [ 4 , 5 , 10 , 12 ]. Similarly, it has been demonstrated that aged mice and rats, maintained in the standard environment of standard laboratory cages, perform worse in learning and memory tasks than those living in an enriched environment [ 13 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…A year later, when cognitive function was evaluated using the MMSE and Global Deterioration Scale (GDS) in a follow-up study, both groups showed similar cognitive decline, but there was no significant difference between the 2 groups. 24 A study in Brazil studied whether living in a specific environment, such as special housing and general housing, had a significant effect on the cognitive function of the elderly people. analyzed the effect of long-term residence on cognitive function in a non-profit shelter (ELSI) for the elderly.…”
Section: Resultsmentioning
confidence: 99%
“…Long-term residents of shelters, special shelters, day care facilities, nursing homes, and non-profit shelters for the elderly were particularly vulnerable. 21,23,24 It was reported that this occurs due to various factors, such as the effect of natural aging, lack of cognitive stimulation, and individual characteristics. However, a study when looking at the cognitive changes of new and existing residents in additional sheltered villages, both groups showed improvement in cognitive function.…”
Section: Discussionmentioning
confidence: 99%